Macroeconomic determinants of sovereign credit ratings and rating changes, and bond yields respond to rating changes - Soh, Wei Chee (2014)
Sovereign credit rating closely measures a country’s international creditworthiness.Previous studies showed that the sovereign credit rating change significantlyimpact to the domestic finance sector. However, the credit rating agencies (CRAs) only reveal the criteria focused in rating assessment, moreover, provided limited information about the variables involved. The public need an indicator in signaling the phenomenon of sovereign rating change. As far as we know, economic is one of the criteria that concerned by CRAs in rating assessments, can be quantified and predicted by the macroeconomic variables. Hence, there is a need to identifythe macroeconomic factor determining the rating and rating change on a timely basis. This study identify the determinants of the sovereign credit ratings and rating changes and determine the asymmetric respond in rating change on procyclicalbehavior from year 2000 to 2011. This study included9 macroeconomics variables in analysis, and extended by using two other qualitative variables, i.e., economic development indicator and economic freedom indicator. To identify the determinants of sovereign rating and rating change, the panel data model and ordered probit model shows similar results and this is the evidence of robustness in the analysis. From the findings,four macroeconomic variablesdeterminants the rating: interest rate, GDP per capita, GDP deflator, and foreign exchange of countries. The unexpected hiking in interest rate attracts hot moneys that cause financial volatility into the local financial market. The GDP per capita is a variable to measure countries’ capability to repaying debts and this supported by previous researchers (Cantor and Packer, 1996; Bissoondoyal-Bheenick, 2005; and Bissoondoyal-Bheenick et al., 2006).The presence of high price level lower the purchasing power; lift up the living cost, and lower the standard of living.A country with high level of foreign reserve promotes exchange rate and financial market stability. The result of the study has indicated that the economic development and the economic freedom of a country is a decisive factor in rating evaluation.Countries with high economic freedom indicate that local residences enjoy more freedom in economic structure transactions. Therefore, advance (developing) economy countries with high (low) GDP per capita, high (low) foreign reserve, high (low) economic freedom, low (high) interest rate, and low (high) inflation will be awarded with high (low) sovereign credit rating. Besides, developing (advance) countries with high (low) GDP per capita, high (low) foreign reserve, high (low) money supply and low (high) interest rate have higher tendency to be rating upgrade (downgrade). Lastly, the event study provides evidence for the asymmetric responses in the bond market returns for upgrade and downgrade events. The results show that the impact of upgrade events is slower and prolonged within event window of (+3, +12). Conversely, the reaction to downgrade events is sharper and last for a short term within event window of (-3, +3). From the findings, sovereign credit rating performs as an indicator of international creditworthiness with foundation. The Standard & Poor’s tend to be open in upgrade evaluations, meanwhile behave conservative in downgrade event assessments.